(untitled) (Bangladesh Agronomy Journal, 2018)
An experiment was carried out in Agronomy field of Sher-e-Bangla Agricultural University, Dhaka to find out the performance of wheat (var. BARI Gom 27) as influenced by time of irrigation and different mulch materials during 2015-2016. Four levels of irrigation viz. control, one irrigation at CRI (crown root initiation) stage, one irrigation at flowering stage and two irrigations each at CRI + flowering stage; and four different mulch materials viz. control, rice straw, rice husk and plastic sheets were considered as treatment variables. The experiment was laid out in a split- plot design with three replications, assigning irrigation to main plot and mulch materials to sub plots. Results showed that time of irrigation and different mulch materials had significant effect on plant characters, yield and yield components of wheat. Two irrigations given at CRI + flowering stage resulted with significantly higher plant height, number of spikelets spike-1, number of grains spike-1, 1000- grain weight, grain yield, straw yield and harvest index over one irrigation and control plots. Among mulch materials, black plastic mulch resulted with significantly higher grain yield of wheat. The highest grains (4.15 t ha-1) and straw yields (4.25 t ha-1) were obtained with two irrigations at CRI and flowering stage with black plastic mulch for achieving higher productivity. Bangladesh Agron. J. 2018, 21(1): 71-76